2015
DOI: 10.1186/s12870-015-0566-6
|View full text |Cite
|
Sign up to set email alerts
|

Natural variants of ELF3 affect thermomorphogenesis by transcriptionally modulating PIF4-dependent auxin response genes

Abstract: BackgroundPerception and transduction of temperature changes result in altered growth enabling plants to adapt to increased ambient temperature. While PHYTOCHROME-INTERACTING FACTOR4 (PIF4) has been identified as a major ambient temperature signaling hub, its upstream regulation seems complex and is poorly understood. Here, we exploited natural variation for thermo-responsive growth in Arabidopsis thaliana using quantitative trait locus (QTL) analysis.ResultsWe identified GIRAFFE2.1, a major QTL explaining ~18… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 38 publications
7
92
1
Order By: Relevance
“…Like others [1416], we observed an inverse relationship between ELF3 functionality and transcript levels of PIF4 and AtHB2 , with larger effects on PIF4 expression. The ELF3 lines with the strongest thermal response ( e .…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Like others [1416], we observed an inverse relationship between ELF3 functionality and transcript levels of PIF4 and AtHB2 , with larger effects on PIF4 expression. The ELF3 lines with the strongest thermal response ( e .…”
Section: Resultssupporting
confidence: 84%
“…Following the recent discoveries that ELF3 is involved with thermal response [1416], we confirmed that ELF3 polyQ variation also affects thermal response phenotypes in a background-dependent fashion. However, we found little support for the hypothesis that the polyQ tract has a special role in temperature sensing.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consequently, both light condition and the circadian clock influence thermomorphogenesis by modulating the level of PIF4 (refs 3, 13). Recent studies have shown that the transcription factor EARLY FLOWERING3 (ELF3), a component of the evening complex (EC) of the circadian clock, represses PIF4 RNA expression and warm temperature induces PIF4 expression by inhibiting ELF3 binding to the PIF4 promoter161718. Furthermore, elf3 -null mutant plants grown under short-day conditions develop long hypocotyls that are insensitive to warm temperature1718.…”
mentioning
confidence: 99%
“…Latitude-specific circadian variation has also been observed in other eukaryotes like plants, birds, and mammals. In Arabidopsis , natural allelic variations are associated with several circadian phenotypes like hypocotyl growth (Coluccio, Sanchez, Kasulin, Yanovsky, & Botto, 2011; Raschke et al, 2015), flowering time (Lempe et al, 2005; Press, Lanctot, & Queitsch, 2016), periodic leaf movements (Michael et al, 2003; Swarup et al, 1999) and temperature compensation (Edwards, Lynn, Gyula, Nagy, & Millar, 2005). These same allelic variations are also associated with the phenotypes for breeding time (Hau, 2001) and diurnal and seasonal variation of hormone secretion (Dawson, King, Bentley, & Ball, 2001; Reierth, Van’t Hof, & Stokkan, 1999) in birds, and seasonal variation of melatonin circadian rhythms (Adamsson, Laike, & Morita, 2016) and latitudinal and seasonal specific qualitative and quantitative variations of sleep (Friborg, Bjorvatn, Amponsah, & Pallesen, 2012) in humans.…”
Section: Introductionmentioning
confidence: 99%